Drug-induced lupus erythematosus - F. Atzeni; M.G. Marrazza; P. Sarzi-Puttini; M. Carrabba (PAGEPress Publications, 2003)
Drug-induced lupus is a syndrome which share symptoms and laboratory characteristics with the idiopathic systemic lupus erythematosus (SLE). The list of medications implicated as etiologic agents in drug-induced lupus continues to grow. The terms used for this condition are lupus-like syndrome, drug-induced lupus erythematosus (DILE) and drug related lupus. More than 80 drugs have been associated with DILE. The first case of DILE was reported in 1945 and associated with sulfadiazin. In 1953 it was reported that DILE was related to the use of hydralazine. Drugs responsible for the development of DILE can divided into three groups, but the list of these drugs is quite long because new drugs are included yearly in the list. The syndrome is characterised by arthralgia, myalgia, pleurisy, rash and fever in association with antinuclear antibodies in the serum. Recognition of DILE is important because it usually reverts within a few weeks after stopping the drug.